Cyclical Variations in Wage Differentials and Unemployment - Ohashi, Isao (Journal of Labor Economics, 1987)
This paper attempts to reformulate in a general equilibrium framework Reder's model, which explains cyclical variations in wage differentials and their general tendencies to narrow. Specifically, I focus on the three aspects of his model: the microeconomic behavior of a firm under imperfect information about labor quality, the mechanism of the economy creating unemployment, and the interaction between wage differentials and unemployment. I also explore its implications for the macroeconomic issues on the characteristics of current unemployment and the question of why aggregate employment fluctuates.